Sull’impotenza - Virno, Paolo (Dialogoi. Rivista di studi comparatistici, 2020)
The purpose of this article is to describe the nature and the features of the powerlessness which characterizes our forms of life. Here is the main thesis: contemporary powerlessness is caused by an overabundance of faculties, capacities, skills that, however, are blocked in their accomplishment. Dynamis without energheia, power (potency) without acts, as Aristotle wrote polemicizing with the philosophers of Megara, supporters of the inseparability of potency and act. I also try to understand the Aristotelian idea that human species has, and therefore is not, its own faculties and abilities. In this dynaminechein, in this having (and not being) our power (potency), is perhaps found the explanation of the radical powerlessness with which we are dealing.